Factibilidad para la implementación de una biblioteca infantil con cuenta cuentos y mini-obras teatrales en la ciudad de Loja - Quizhpe Montoya, Marjorie Alejandra (2016)
The present project developed in Loja's city with the intention of creating a new company of education that helps to rescue the values and the habits of the reading, likewise like to stimulate and promote the intellectual motricidades from very early ages in the children / as between the ages of three to ten years. And in addition as new alternative of investment for the small and medium investors. The general target of the present thesis consists of determining the FEASIBILITY FOR THE IMPLEMENTATION OF AN INFANTILE LIBRARY WITH STORIES AND MINI-THEATER IN THE CITY OF LOJA; for which we proceeded to realize four main studies that have allowed determining its feasibility. To expire with the objective present, investigation methods were used like the analytic one that allowed to compile the information by means of the interview and the surveys, the deductive method that allowed to prepare the review of literature that has the project and describe the general precedents of the service, the inductive method allowed analyze and interpret the information obtained from the sample projecting for the entire population of lojanas family. Also applied the techniques the interview and the survey across the segmentation of market that in this case were the families of the city of Loja in a number of 49.803 families for the basic years of the project with a growth rate of 2, 65% according to information of the INEC, of which was realized a size of the sample that gave like turned out 381 surveys to be applied to the above mentioned segmentation. 6 In the results there was applied survey to the applicants and an interview to the offer of Loja´s city. Within the discussion a market study where the population under study that resulted there 45.819 families who have children / as between the ages of three to ten years and with an average of 2 children / as was established was by family was obtained in the city of Loja there are 91.638 children/as between those ages, this figure could be determined that potential demand is 6´153.884 use of service a year, the actual demand is 1'260.939 use service year 1'122.229 demand Effective use of service a year, also was considered, and thus may be obtained 1'108.657 unmet demand for services for the first year, then the marketing plan, determining the set service, price, place, promotion and advertising service; The technical study is detailed size; where capacity utilization is 71,23% of the installed capacity and the location of the company will be located in the parish of the Sagrario, in Bolivar streets between Colon and Jose Antonio Eguiguren, from the city of Loja .; In the administrative and legal study this company will be legally constituted as Unipersonal Limited Liability Company, and its name will be "THE FUTURE OF MINI EINSTEINS M.Q." E.U.R.L.; is presented the organizational charts and functions manuals In the financial study the project reaches an investment for 23.336,24 dollars and it will be financed by an internal contribution that is 57,15% of the whole of the investment that corresponds to 13.336,24 dollars and a loan that will mainta in the project with the National Bank of Promotion 7 42,85 % that corresponds to 10. 000 dollars to 5 years term to 11 % of annual interest. As for the financial evaluation it is necessary to mention that the project is a feasible position that this one has a Clear Current Value (GO) positive for 15.602,10 dollars, what indicates that the project or investment is suitable. For the present project the Internal Valuation of Comeback (TIR) is a 29,02%, being this satisfactory value to realize the project, the Period of capital Recovery (PRC) is 3 years, 7 months and 20 days, as for the Relation Benefit / cost(R B/C) is 1,12 dollars, which it is deduced that as every inverted dollar the company will have a utility of 12 cents of dollar, while the sensibility analysis determined that the company supports an increase of up to 3,26% in its costs giving a whole of 0,99; and a decrease of 2,94% in its income giving a whole of 0,99 for which the project is feasible, whose conclusions and recommendations like that determine it, there being enclosed the bibliography consulted with its respective annexes.